Identification of the Fluvirucin B2 (Sch 38518) Biosynthetic Gene Cluster from Actinomadura fulva subsp. indica ATCC 53714: substrate Specificity of the β-Amino Acid Selective Adenylating Enzyme FlvN. Issue 5 (3rd May 2016) - Miyanaga, Akimasa; Hayakawa, Yuki; Numakura, Mario; Hashimoto, Junko; Teruya, Kuniko; Hirano, Takashi; Shin-ya, Kazuo; Kudo, Fumitaka; Eguchi, Tadashi
Abstract: Fluvirucins are 14-membered macrolactam polyketides that show antifungal and antivirus activities. Fluvirucins have the β-alanine starter unit at their polyketide skeletons. To understand the construction mechanism of the β-alanine moiety in fluvirucin biosyntheses, we have identified the biosynthetic cluster of fluvirucin B2 produced from Actinomadura fulva subsp. indica ATCC 53714. The identified gene cluster contains three polyketide synthases, four characteristic β-amino acid-carrying enzymes, one decarboxylase, and one amidohydrolase. We next investigated the activity of the adenylation enzyme FlvN, which is a key enzyme for the selective incorporation of a β-amino acid substrate. FlvN showed strong preference for l -aspartate over other amino acids such as β-alanine. Based on these results, we propose a biosynthetic pathway for fluvirucin B2 . Graphical abstract: : Proposed biosynthetic pathway for fluvirucin B2